Fabrication and characterization of ZnMgO nanowalls grown on 4H‐SiC by molecular beam epitaxy. Issue 1 (19th December 2018) - Pietrzyk, Mieczyslaw A.; Wierzbicka, Aleksandra; Stachowicz, Marcin; Jarosz, Dawid; Kozanecki, Adrian
Abstract : The crystal quality of ZnMgO nanowalls grown on 4H‐SiC substrates has been investigated by X‐ray diffraction. Abstract : Control of nanostructure growth is a prerequisite for the development of electronic and optoelectronic devices. This paper reports the growth conditions and structural properties of ZnMgO nanowalls grown on the Si face of 4H‐SiC substrates by molecular beam epitaxy without catalysts and buffer layers. Images from scanning electron microscopy revealed that the ZnMgO nanowalls are arranged in parallel rows following the stripe morphology of the SiC surface, and their thickness is around 15 nm. The crystal quality of the structures was evaluated by X‐ray diffraction measurements.